The easter semiotics of the “albazin pie” - Vladimir Pushkarev; Vladimir Trukhin (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
This study is devoted to one of the episodes of the Russian-Manchu conflict of the 17th century, when the head of the garrison of the Albazin fortress, which had been blocked by the Manchus for a long time, sent a pie to the camp of his enemies. This case caused a wide response in publications devoted to the history of this confl ict in the 18th century, and continues to excite researchers today. The interpretation of these events, made by G.F. Miller, became canonical, but a careful study of the circumstances of the incident leads to the conclusion that it is historically inconsistent. A detailed analysis of the events of this period makes it possible to supplement this episode with details, which in turn make it possible to identify other motives that prompted the defenders of the fortress to commit this act. To understand the psychology of the Albazinians, it is important to take into account the following circumstances: despite signifi cant combat and non-combat losses caused by disease, the garrison retained its combat capability; by this time, a decision had already been made to conclude a truce between the confl icting parties for peace negotiations, in connection with which the Manchus had to lift the blockade of the fortress and retreat. But most importantly, most of the Albazin defenders were Christians, and the presentation of the cake took place on the day of the celebration of the Resurrection of Christ. Therefore, the most important aspect of a diff erent interpretation of these events is that this pie had a ritual significance, and when presenting the Easter pie to their opponent, the Albazinians could not help but invest in this act the symbolic meaning of their involvement in the divine power of the Resurrection as a symbol of the victory of life over death.